Pengaruh Religiusitas, Kepercayaan, Kemudahan, dan Pemahaman Digital terhadap Minat Membayar Zakat, Infak, dan Sedekah (ZIS) Secara Digital - Sharla Putri Rania; Edi Susilo (ITB AAS INDONESIA Surakarta, 2026)
The rapid development of digital technology has created significant opportunities to optimize the collection of zakat, infaq, and alms (ZIS) through digital platforms. However, the utilization of digital ZIS in Indonesia remains far below its national potential. This study aims to analyze the influence of religiosity, trust in digital ZIS institutions, ease of application use, and understanding of digital zakat on public interest in paying ZIS digitally. This research employs a quantitative approach with an explanatory research design. Data were collected through an online questionnaire from 100 Muslim respondents in Indonesia using purposive sampling. Data analysis was conducted using multiple linear regression after validity, reliability, and classical assumption tests. The results show that religiosity, trust, ease of use, and understanding of digital zakat have a positive and significant effect on the intention to pay ZIS digitally, both partially and simultaneously. Among these variables, understanding of digital zakat has the strongest influence. The model explains 59.7% of the variance in digital ZIS payment intention. These findings highlight the importance of integrating religious, institutional, technological, and cognitive factors in promoting the adoption of digital ZIS payments in Indonesia.